The psychometric evaluation of the Italian version of the Surgical Fear Questionnaire in adult patients waiting for major cardiac surgery - Damico, Vincenzo; Cossalter, Luca; Murano, Liana; D'Alessandro, Antonella; Fermi, Lara; Milani, Margherita; Demoro, Giuseppe (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background and aim. Preoperative surgical fear is an emotional reaction that can be observed in many patients who are waiting to undergo a surgical procedure. The Surgical Fear Questionnaire was originally developed to determine the level of fear in patients who are expected to undergo elective surgery. This study aims to test the validity and reliability of this Italian version in a population of patients waiting for major cardiac surgery.Study design. Methodological research model.Methods. The population of this methodological study included the patients who presented to Lecco Hospital in Italy between January 2022 and October 2023 and were scheduled to undergo valve surgery, aortic surgery or coronary surgery; the sample involved 416 patients who met the inclusion criteria.Results. Results of the analyses showed that the Surgical Fear Questionnaire can be used with two subscales; the “Surgical Fear Questionnaire-S”, which shows the fear of the short-term consequences of cardiac-surgery, and the “Surgical Fear Questionnaire-L”, which shows the fear of the long-term consequences of cardiac-surgery. The mean score of the patients was 26.32+9.23 on the former, 27.62+11.89 on the latter, and 53.94+19.16 for the entire questionnaire. The Cronbach’s α coefficient was 0.952 for the “Surgical Fear Questionnaire-S”, 0.920 for the “Surgical Fear Questionnaire-L”, and 0.914 for the entire questionnaire.Conclusion. Based on the validity and reliability tests, we consider the questionnaire adaptable to the Italian reality, specifically to the population waiting for major cardiac surgery.